¿Y dónde están las rubias? White chicks - Alvarez, Rick; Wayans, Keenen Ivory; Revolution Studios (2004)
Dos agentes del FBI van de manera clandestina a un hotel en un esfuerzo por proteger a la hermana heredera de Wilson de una conspiración e intento de secuestro.
Copyright: Revolution Studios Distribution Company, LLC, employer for hire. NM: motion picture. PREV.: Screenplay prev. reg. 2003, PAu2-813-838; prev. pub. musical compositions, sound recordings, posters & artwork. DCR 2004; PUB 23Jun04; REG 24Jun04; PA1-222-517.
Fuentes usadas: copyright data sheet; copyright data base; Internet Movie database.
Summario tomado de Internet Movie database, 5/3/2005.
Original music, Teddy Castellucci ; cinematography, Steven Bernstein ; film editing, Jeff Gourson and Stuart H. Pappe.
Shawn Wayans, Marlon Wayans, Jaime King, Frankie Faison, Lochlyn Munro, John Heard, Busy Philipps, Terry Crews, Brittany Daniel, Eddie Velez, Jessica Cauffiel, Maitland Ward, Anne Dudek.
MPAA rating: PG-13 for crude and sexual humor, language and some drug content.
Keywords: Comedia -- Videograbaciones; Comedia -- Largometraje para televisión; Delincuencia -- Largometraje para televisión